The Effect of Young Coconut Water on Blood Pressure in Middle-Aged Adults (45–59 Years) with Hypertension in RT005/RW012, Taman Mangu Indah Residential Area, South Tangerang - Raidah Shahirah Cahyadi; Nila Rostarina; Achirman Achirman; Gaung Eka Ramadhan (Asosiasi Dosen Muda Indonesia, 2026)
Hypertension is a leading contributor to cardiovascular morbidity and mortality and is often undetected until complications occur. Community-friendly, affordable non-pharmacological approaches are therefore needed to support blood pressure control alongside standard therapy. Objective: This study aimed to examine the effect of young coconut water on blood pressure among middle-aged adults (45–59 years) with hypertension in RT005/RW012, Taman Mangu Indah Residential Area, South Tangerang. Methodology: This quantitative study used a quasi-experimental pretest–posttest design without a control group. A total of 21 participants received young coconut water (250 cc) twice daily (morning and afternoon) for five consecutive days. Blood pressure was measured before and after the intervention using a calibrated sphygmomanometer, and changes were analyzed using paired t-tests. Findings: Young coconut water consumption was associated with significant reductions in both systolic and diastolic blood pressure. Morning measurements showed decreases from 150.71 to 140.95 mmHg (systolic) and from 96.19 to 90.48 mmHg (diastolic) (p = 0.001). Afternoon measurements decreased from 145.24 to 132.86 mmHg (systolic) and from 96.19 to 85.24 mmHg (diastolic) (p = 0.001). The afternoon reductions appeared greater than those observed in the morning. Implications: Young coconut water may serve as an accessible, low-cost complementary nursing intervention to support community-based hypertension management. The findings may inform community health education and practical programs to improve blood pressure control among middle-aged adults. Originality: This study provides neighborhood-based evidence using a feasible twice-daily regimen over five days and highlights potential differences in blood pressure reduction between morning and afternoon administrations, offering implementation-oriented insight for community nursing practice.